Political Economy of Agricultural Trade Interventions in Africa - Bates, Robert H.; Block, Steven (World Bank, Washington, DC, 2017)
This paper uses new data on agricultural policy interventions to examine the political economy of agricultural trade policies in Sub-Saharan Africa. Historically, African governments have discriminated against agricultural producers in general (relative to producers in non-agricultural sectors), and against producers of export agriculture in particular. While more moderate in recent years, these patterns of discrimination persist. They do so even though farmers comprise a political majority. Rather than claiming the existence of a single best approach to the analysis of policy choice, the authors explore the impact of three factors: institutions, regional inequality, and tax revenue-generation. The authors find that agricultural taxation increases with the rural population share in the absence of electoral party competition; yet, the existence of party competition turns the lobbying disadvantage of the rural majority into political advantage. The authors also find that privileged cash crop regions are particular targets for redistributive taxation, unless the country's president comes from that region. In addition, governments of resource-rich countries, while continuing to tax export producers, reduce their taxation of food consumers.